2019
DOI: 10.1039/c9ra02889g
|View full text |Cite
|
Sign up to set email alerts
|

The influence mechanism of nanoparticles on the dielectric properties of epoxy resin

Abstract: The free volume theory and trap model of nano-modified composite materials were combined to explain the breakdown voltage mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The charges injected by the electrode can pass through the potential barrier into the conduction band through the Schottky effect and be captured by the trap in the forbidden band. 30 The relaxation time of captured charges in traps is mainly determined by trap energy level and trap energy density. The larger trap energy level and density, the longer the relaxation time would be.…”
Section: Resultsmentioning
confidence: 99%
“…The charges injected by the electrode can pass through the potential barrier into the conduction band through the Schottky effect and be captured by the trap in the forbidden band. 30 The relaxation time of captured charges in traps is mainly determined by trap energy level and trap energy density. The larger trap energy level and density, the longer the relaxation time would be.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the excessive ZnS weakened the liquidity of epoxy coatings, resulting in particle agglomeration (Figure 6i) and decrease of anti-wear property. 44,45 F I G U R E 1 0 The effect of graphite content on the tribological performances of epoxy composite coatings exposed in dry state at100 C: Figure 11c shows some grooves on the surface of TTG7C parallel to the sliding direction, and this was because the process of fiber thinning!cracking!breakage brought about the fatigue damage of coating. Furthermore, it can be observed that plenty of parallel and compact scratch lines occurred on the surface of grinding ball (Figure 11d), indicating the serious interface damage due to the high stiffness of SCFs.…”
Section: Effect Of Zns On the Tribological Propertiesmentioning
confidence: 99%
“…However, the dielectric constants of most polymers are generally below 10, which seriously affects their energy storage density 14 . By introducing nanofillers into the polymer matrix, the excellent physicochemical properties of two materials and new functions can be obtained simultaneously 15–19 . In this regard, a large number of researches have been conducted to enhance the dielectric constant of polymers by selecting high dielectric constant ceramic materials or conductive fillers.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a large number of researches have been conducted to enhance the dielectric constant of polymers by selecting high dielectric constant ceramic materials or conductive fillers. Typical nanocomposites randomly distribute nanofillers in polymer matrix by specific means, enhancing mechanical properties, thermal conductivity, and high temperature resistance of polymers 19–24 . However, with the development of industrial technology, traditional polymer nanocomposites can hardly meet the requirements in the domain of high energy storage.…”
Section: Introductionmentioning
confidence: 99%